Temporal relations in Danish tautosyllabic CV sequences with stop consonants - Fischer-Jørgensen, Eli (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
This paper presents some facts about the duration of closure and open interval in Danish stop consonants (5.1 - 5.2). 5.3 deals specifically with the relation between durations of closure, open interval and following vowel (1) in ptk vs. bdg, (2) depending on place of articulation of the consonant, (3) in connection with long and short vowels, (4) with high and low vowels, and (5) with rounded and unrounded vowels. In section 6 it is discussed whether the relations found are due to compensation within the CV sequence or to specific production mechanisms. It is suggested that only vowel length in (1) may be due to compensation.